2019
DOI: 10.1108/ijbpa-01-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost retrofit packages for residential buildings in hot-humid Lagos, Nigeria

Abstract: Purpose The purpose of this paper is to develop a set of affordable retrofit packages that can be applied to existing residential buildings in hot-humid regions to improve occupants’ thermal comfort and reduce energy consumption. Design/methodology/approach A critical review of relevant literature to identify passive design strategies for improving thermal comfort and reducing energy consumption in hot-humid climates with focus on the building envelope was conducted in addition to a simulation study of an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The prescriptive performance covers specifications for technical installations, passive designs (lighting, daylighting/ventilation-WWR, roof insulation-thermal massing, shading and active energy equipment specifications) and active energy equipment. Even though prescriptive performance is inept to ascribe energy performance (Arent, 2016), studies that benchmarked the potential energy-savings of the listed interventions in Nigeria are enormous (Gyoh et al , 2013; Arup and Design Genre, 2016; Onyenokporo and Ochedi, 2019). The code, published in 2017, allows a window of two years for voluntary compliance using either prescriptive or performance compliance methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The prescriptive performance covers specifications for technical installations, passive designs (lighting, daylighting/ventilation-WWR, roof insulation-thermal massing, shading and active energy equipment specifications) and active energy equipment. Even though prescriptive performance is inept to ascribe energy performance (Arent, 2016), studies that benchmarked the potential energy-savings of the listed interventions in Nigeria are enormous (Gyoh et al , 2013; Arup and Design Genre, 2016; Onyenokporo and Ochedi, 2019). The code, published in 2017, allows a window of two years for voluntary compliance using either prescriptive or performance compliance methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research draws from the gap in the dearth of knowledge about the GCP in the use of energy-efficient construction approach in Nigeria from the normative literature. Onyenokporo and Ochedi (2019) validated the performance of selected passive low-cost energy retrofit strategies in Lagos, Nigeria. Akin to other studies from this region, the study charitably reported the expenditures associated with the introduction of non-certified Passive Design Strategies (PDS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The computer modeling techniques have been widely promoted in the current literature as a useful, accurate, efficient, and reliable tool for building optimization (Olaniyan, 2012). They save time and money compared with a range of available quantitative research methods (Onyenokporo and Ochedi, 2019). In this study, a simulation study using the EnergyPlus simulation tool in DesignBuilder was adopted to test a selected building prototype that represents the dominant residential building for an average low-and middle-income earners.…”
Section: Introductionmentioning
confidence: 99%
“…The first goal of NZEB is to improve the energy efficiency of a building to the ultimate level (Heinze and Voss, 2009; Musall et al , 2010; Zhao et al , 2009). The energy efficiency of any building is influenced by some passive design strategies such as thermal insulation, window glazing types, orientations, natural ventilation, window-to-wall ratio and daylighting (Onyenokporo and Ochedi, 2019; Pless and Torcellini, 2010). The effectiveness of the above stated passive design technologies on energy efficiency is influenced by the microclimatic condition of various regions of the world significantly.…”
Section: Introductionmentioning
confidence: 99%